Effect of ionizing radiated gladiolus (Gladiolus grandifloras) on vase life attributes of various cultivars - RAWAT, ANAND SINGH; BHUJ, B D; SRIVASTAVA, RANJAN; CHAND, SATISH; SINGH, N K; BISHT, YASHPAL SINGH; BHATT, RAJENDRA (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during winter (rabi) seasons of 2018–19 (vM2), 2019–20 (vM3) and 2020–21(vM4) at Govind Ballabh Pant University of Agriculture and Technology, Pantnagar, Uttarakhand to evaluate the effect of gamma rays treated gladiolus (Gladiolus grandiflorus Andrews) on the post-harvest of different varieties along with their interaction for different qualitative traits The result showed that Praha was best cultivars for days to first floret opening, highest number of florets per spikes, highest number of open florets per spikes, rachis length and weight loss followed by cultivar Candyman for highest diameter of lowest floret, highest vase life and highest water uptake by spikes. Among the different gamma doses, the minimum days to first floret opening, the highest diameter of first floret, the days to first floret withering, the number of florets, the number of open florets, the rachis length, vase life, water uptake by spikes and the weight loss were recorded in non-irradiated corms. Among interaction, V2G0 (Praha + control) showed best result for days to first floret opening, total number of florets per spike, total number of open florets/spike and rachis length. Most important characters, vase life was positively correlated with rachis length at 5.0 and 6.0 Kr respectively, total number of florets/spike and total number of open florets/spike at 5.0 Kr. Study concluded that gamma rays affect the qualitative as well quantitative traits of gladiolus and do not have positive effect on vase life attributes.